2021
DOI: 10.1007/s10551-021-04833-0
|View full text |Cite
|
Sign up to set email alerts
|

Can Creativity Be a Collective Virtue? Insights for the Ethics of Innovation

Abstract: Virtue accounts of innovation ethics have recognized the virtue of creativity as an admirable trait in innovators. However, such accounts have not paid sufficient attention to the way creativity functions as a collective phenomenon. We propose a collective virtue account to supplement existing virtue accounts. We base our account on Kieran’s definition of creativity as a virtue and distinguish three components in it: creative output, mastery and intrinsic motivation. We argue that all of these components can m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…The question already posed above can be reformulated in terms of this character trait: is care a necessary condition for orienting towards the goals of the governance frameworks such as responsible innovation or is it already a necessary condition of any innovation? Building on others' arguments [6,50,51], we submit that care is a necessary condition for responsible innovation, including within micro-level practices. For example, Xavier Pavie [52] argues that care requires the consideration of "the essential interdependence between the innovator and the citizen."…”
Section: Moral and Poietic Virtuesmentioning
confidence: 92%
See 1 more Smart Citation
“…The question already posed above can be reformulated in terms of this character trait: is care a necessary condition for orienting towards the goals of the governance frameworks such as responsible innovation or is it already a necessary condition of any innovation? Building on others' arguments [6,50,51], we submit that care is a necessary condition for responsible innovation, including within micro-level practices. For example, Xavier Pavie [52] argues that care requires the consideration of "the essential interdependence between the innovator and the citizen."…”
Section: Moral and Poietic Virtuesmentioning
confidence: 92%
“…Group virtues have been discussed in social philosophy, social epistemology, and business ethics in terms of "group moral virtues," "collective epistemic virtues" and, in the case of creativity, "collective virtues" cf. [10][11][12][13][14][15][16][17][18][19]44,51]. Granted that there are these group virtues, a reinterpretation of such a case involving vices could be given.…”
Section: Collective Virtues?mentioning
confidence: 99%
“…Of these, one turned out to be the most popular -Creativity and Innovation Management -in which three articles were published. Only three publications appeared in journals ranked above 150 h-index points: Astola et al (2021) in the Journal of Business Ethics, Brown and Anthony (2011) in the Harvard Business Review and Lee and van Dolen (2015) in the Information & Management. The average number of h-index points was 74.…”
Section: Descriptive Analysismentioning
confidence: 99%
“…The analysis of data sources observed a uniform approach to research, i.e., the use of mixed primary and secondary sources. Two articles stood out: Brown and Anthony (2011) used only raw data, and Astola et al (2021) used secondary data. Scientific publications differed in data-obtaining methods.…”
Section: Journal Namementioning
confidence: 99%
“…The creative process model of Amabile (1996) defined creativity as the generation of new and useful ideas or products. The novelty of ideas or products is usually formed in the individual positive psychological processes, and the best ideas often come from unexpected sources ( Astola et al, 2021 ). Prior research has indicated that employee creativity can be triggered by factors related to their self-awareness ( Liu et al, 2016 ).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%